Test techniques of photonic integrated circuits for PON networks - Fontes, Alexandre Rui Reis (2020)
Optical communications are part of our daily routines being the basis of most of nowadays telecommunications infrastructures, standing out for the quality and e ciency concerning the data transmission. Thanks to the technological advances, there is a need to develop these communication infrastructures in order to satisfy the consumer's needs. Passive Optical Network (PON) is one of the architectures used to bring optical ber to the nal consumer. Its implementation and conservation are inexpensive, and the bandwidth is divided by the connected users. However, with the increasing access to information through digital channels it is necessary to optimize costs, increase its rate, widen the amount of information and develop the quality of the data transmission. In the future, the use of integrated optical circuits (PIC) will allow the improvement of the PON networks, since they incorporate di erent optical components with various functions. The characterization of these chips is still in an early stage in our laboratories and needs to be optimized. Thus, this work addresses tests that have been carried out to establish a testing model and present a generic test setup. This can be used as a tool with all the necessary stages to the completion of the tests. It starts with the theoretical framework about PON and the integrated optical circuits. Then, there is a chapter dedicated to measures theory and proper treatment of data obtained in an experiment. Some of the PICs tests performed in the laboratory are presented. Finally, a generic test setup and a test model are suggested. As shown in this essay, the recommended setup is less time consuming, and it o ers a higher quality in the data receiving and processing.